SYNTHESIS, CHARACTERIZATION AND ANTIMICROBIAL ACTIVITY OF AZOL SUBSTITUTED DERIVATIVES (International Journal of Pharmaceutical Sciences and Drug Research, 2009)
A series of dichlorides (Ia-h) followed by 1, 3, 4-Thiadiazol-2-Amine (II a-h) were synthesized by using various dicarboxylic acids(a-h), the further reaction of (I) was carried out with thiosemicarbazide in presence of sulphuric acid to converted into corresponding 1, 3, 4-Thiadiazol-2-Amine (II a-h) The structures of these compounds were confirmed by IR, NMR and Mass spectral analysis. The newly synthesized compounds were evaluated for the antibacterial and antifungal activity. The results show that compound (IIa), (IIe), (IIf) and (IIh) exhibited moderate to good antibacterial and antifungal activity at 5-100 mcg/ml.